2021
DOI: 10.1002/slct.202100831
|View full text |Cite
|
Sign up to set email alerts
|

Interface Structure and Dynamics in Polymer‐Nanoparticle Hybrids: A Review on Molecular Mechanisms Underlying the Improved Interfaces

Abstract: In a nano‐assembly of soft polymer chains and hard filler nanoparticles (NPs), the intermolecular interactions at the polymer‐filler interface lead to variations in viscoelastic properties in the vicinity of the NP surface. However, unravelling the molecular parameters controlling the entropic and enthalpic interactions, including polymer chain conformation, dynamics, dispersion mechanisms and confinement effects across the interfacial region, has been remote and challenging. Even though the polymer‘s molecula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 158 publications
3
25
0
Order By: Relevance
“…Structural distortions of tetrahedral liquids near interfaces can be further analyzed on the basis of the tetrahedral order parameter Q . For water in silica pores, it was observed that the strongly reduced hydrogen bonding at the interface is accompanied by notably reduced tetrahedral order. , For larger molecules, in particular, polymers, the conformation can differ near an interface and in the bulk. For example, it was reported that polymer chains are flattened parallel to solid surfaces and shrunk in the perpendicular direction …”
Section: Structural Distortions At Interfacesmentioning
confidence: 99%
See 2 more Smart Citations
“…Structural distortions of tetrahedral liquids near interfaces can be further analyzed on the basis of the tetrahedral order parameter Q . For water in silica pores, it was observed that the strongly reduced hydrogen bonding at the interface is accompanied by notably reduced tetrahedral order. , For larger molecules, in particular, polymers, the conformation can differ near an interface and in the bulk. For example, it was reported that polymer chains are flattened parallel to solid surfaces and shrunk in the perpendicular direction …”
Section: Structural Distortions At Interfacesmentioning
confidence: 99%
“…In recent years, computer simulations have developed into a powerful tool for confinement studies. ,, Particular advantages are full control over the confinement properties and the manifold possibilities for position-resolved and component-selective analyses of the liquid behaviors, which are offered by the knowledge of all particle trajectories. The simulation method of choice depends on the kind of problem under investigation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The interface in nanocomposites is defined as a region in the neighborhood of the nanoparticles’ surface where the properties of the polymer are different compared with that of the matrix [ 44 , 45 ]. The interface thickness in polymer nanocomposites with nanoparticles of 20–50 nm was estimated to be in the range of 10–30 nm by Tanaka et al [ 44 ] and Smith et al [ 45 ], while thicknesses lower than 10 nm were considered in other works [ 46 , 47 ]. For an estimation of the interface thickness closer to that occurring in our nanocomposites, the surface of E5, the nanocomposite with the smallest amount of silica nanoparticles and the least agglomerations, was investigated by atomic force microscopy (AFM) using a MultiMode 8 equipment from Bruker (Madison, WI, USA).…”
Section: Resultsmentioning
confidence: 99%
“…The composite with the modified interfacial interaction gives a higher glass transition temperature and better dynamic properties . The detailed molecular mechanisms underlying the improved interface structure can be found in the review article by Sattar . Although, these studies successfully developed the methods for well dispersion of silica in a rubber matrix by the conventional dry mixing process.…”
Section: Introductionmentioning
confidence: 99%